"But you said 'four sheep' …!": (sign) language, ideology, and self (esteem) across generations in a Mayan family. (January 2016) - Haviland, John
Abstract: A first generation family sign language, dubbed Z, emerging in a single extended household in an otherwise Tzotzil-speaking community of indigenous peasants in highland Chiapas, Mexico, provides an example of both rapid language creation and change and of the evolution of ideologies of appropriate language form and use in even such a minimal speech/sign community. Adding the new sign language to (the bottom end of) an existing inventory of differentially evaluated language varieties, including Tzotzil and Spanish, positions the signers with respect not only to hearing speakers, but to one another. The most striking contrast presented is between the oldest fluent signer—the first deaf person in her community—trapped by her sign language, and the youngest—her hearing son—propelled beyond it. Highlights: Sign language can emerge in even a small cohort of three deaf siblings. Language "choices" both reflect and project individual life trajectories. Sign forms are themselves miniature chronotopes, with biographical overtones. Language divisions and social divisions are mutually constitutive in even a minimal language community. Metalinguistic attitudes mutually reinforce social evaluations.